Investigation of heat transfer and pressure drop for a multiple‐started ribbed pipe using large‐eddy simulation. Issue 11 (1st July 2022) - Kügele, Simon; Renze, Peter; Dietl, Jochen; Grützner, Thomas
Abstract: Turbulent heat transport phenomena in multiple‐started helically ribbed pipes are investigated. Such structures are applied to enhance heat transfer in various technical systems. A large‐eddy simulation (LES) approach is used to model the turbulent flow field. The simulation results for heat transfer and pressure loss are in good agreement with available experimental data and the simulation model is successfully validated for complex surface geometries. For a better understanding of the impact of the wall structures on the turbulent transport processes, local profiles of the relevant flow variables values are investigated. Thus, the specific mechanism of the heat transfer enhancement can be explained and a knowledge‐based optimization of innovative structures is possible.